BERMUNCULANNYA MASALAH KESEHATAN MASYARAKAT:TANTANGAN UNTUK MENGORGANISASI KERJA SAMA DAN KEMITRAAN GLOBAL = THE EMERGING PUBLIC HEALTH PROBLEMS IN INDONESIA ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract The emergence of public health problems in Indonesia has posed a great challenge for the Government of Indonesia as well as international health dan development agencies. In its 40th anniversary, The Faculty of Public Health University of Indonesia (FKM UI) initiated and organized a roundtable discussion on August 24, 2005. The theme of the discussion was The Emerging Public Health Problems in Indonesia : Organizing Concerted Efforts dan Partnership Opportunities. The purpose of the discussion was to : (1) identify the emerging public health problems, (2) strategy to cope the problems, (3) identify opportunity to make collaboration dan partnership with the funding agencies to cope with the public health challenge. International experience showed that the developed world has not been able to conquer the infectious diseases while facing the lifestyle-related non-infectious diseases such as heart disease. In the meantime, new emerging infectious diseases have appeared, such as SARS dan Avian Influenza. Indonesia has been challenged to keep dan to improve the quality of health while struggling to recover from the impacts of prolonged economic dan political crises. The condition was worsen when Aceh was striken by the tsunami of the Andaman Nicobar earthquake. Resources from all over the world have been deployed to the region to recover from the devastated impacts including poor sanitation, environmental pollution and the absence of clean dan decent living. When the situation was undercontrol, new infectious diseases such as SARS, Avian Influenza have been striking the public internationally. This phenomenon indicates that public health has been crossing the border of country domination and require concerted effort to cope with this situation. The School of Public Health is being challenged to be strategically responsive and strategic to contribute in the mainstream of the effort to attack this global problem.